A Nomogram for Predicting the Risk of Death in Patients with Prolonged Hospital Stays in Internal Medicine Wards: A Retrospective Study - Pan H; Liu X; Wang B; Hang H; Ye S (International Journal of General Medicine)
Huiqing Pan,1,* Xinran Liu,2,* Bing Wang,1 Hua Hang,3 Sheng Ye1 1Emergency Department, The Second Affiliated Hospital of Wannan Medical College, Wuhu, Anhui, People’s Republic of China; 2Graduate School, Wannan Medical College, Wuhu, Anhui, People’s Republic of China; 3Medical Records Management Department, The Second Affiliated Hospital of Wannan Medical College, Wuhu, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sheng Ye, Emergency Department, The Second Affiliated Hospital of Wannan Medical College, 10 Kangfu Road, Jinghu District, Wuhu, Anhui, People’s Republic of China, Email yesheng0553@163.comObjective: Prolonged hospital length of stay (PLOS) is associated with adverse outcomes, including increased healthcare costs, higher risk of complications, and increased mortality. This study aimed to investigate the relationship between PLOS and mortality among patients hospitalized in internal medicine wards and to develop a nomogram to predict the risk of death in this patient population.Methods: This retrospective study included patients hospitalized for more than 30 days in internal medicine wards between January 1, 2022, and December 31, 2022. Multivariate logistic regression analysis was used to identify independent risk factors for in-hospital mortality. The nomogram was constructed based on the independent factors. Calibration curves and receiver operating characteristic (ROC) curves were used to evaluate the predictive performance of the nomogram, and decision curve analysis (DCA) was conducted to assess its clinical utility.Results: A total of 1042 patients were included in this study, resulting in a mortality rate of 10.17%. Multivariate logistic regression analysis showed that age (OR=1.043, 95% CI: 1.026– 1.061, P< 0.001), tumor (OR=2.274, 95% CI: 1.441– 3.589, P< 0.001), blood transfusion (OR=4.667, 95% CI: 2.932– 7.427, P< 0.001), ADL score (OR=0.966, 95% CI: 0.952– 0.981, P< 0.001) and MNA-SF score (OR=0.825, 95% CI: 0.760– 0.895, P< 0.001) as independent risk factors for mortality among patients hospitalized in internal medicine wards. The nomogram constructed using these factors demonstrated well discriminatory ability, with an AUC of 0.803 (95% CI: 0.761– 0.846). Decision curve analysis further validated the clinical utility of the nomogram, highlighting its potential to improve risk assessment and guide clinical decision-making.Conclusion: This nomogram effectively evaluates the risk of death for prolonged hospitalization of patients in internal medicine wards and holds significant potential for promotion in clinical practice.Keywords: prolonged hospital length of stay, internal medicine wards, ADL score, MNA-SF score, in-hospital mortality